1998
DOI: 10.1063/1.122076
|View full text |Cite
|
Sign up to set email alerts
|

Near-field optical imaging of light propagation in semiconductor waveguide structures

Abstract: We have investigated light propagation in optical devices by near-field scanning optical microscopy (NSOM) at the telecommunication wavelength of 1.55 μm. NSOM images obtained on the top of channel waveguides measure the mode profile perpendicular to the propagation direction and show a modulation of intensity along this direction. This modulation demonstrates the periodic variation of the mode size predicted for the propagation in small guides and marks the direction of propagation. We show that NSOM analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
24
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 8 publications
4
24
0
2
Order By: Relevance
“…NSOM studies of waveguides have demonstrated evanescent field decay [9], standing modes [10], and recently observed a modulation in the propagation direction [11] due to the Tien effect [12]. To the best of our knowledge, our measurements provide the first observation of standing modes in a single mode waveguide, as well as the first determination of all components of the propagation vector [13].…”
Section: Introductionmentioning
confidence: 63%
“…NSOM studies of waveguides have demonstrated evanescent field decay [9], standing modes [10], and recently observed a modulation in the propagation direction [11] due to the Tien effect [12]. To the best of our knowledge, our measurements provide the first observation of standing modes in a single mode waveguide, as well as the first determination of all components of the propagation vector [13].…”
Section: Introductionmentioning
confidence: 63%
“…$, NSOMj Ï G; ";öB ò R ;çê ÿö G; > ®bae B· ;öB B > ®º ² ¶~ ;ç Ö ê r > ®² B. [7] ae.rae~ &N º B7² ¶~ B7 ßWj G;~º ãÖ [8][9][10] f 7 ê2~ Rö ;W>º ö:JÎÞ 2¢ G ;~ *2 ßWj V~º ãÖ [1][2][3][4] ¾*Ú" > ®. f PMT(photomultiplier tube)¢ ¦ÂV ÒÏ > ®º 633 nmöB 830 nm~ 2Ë 'ö &¦ª ÷7>î b, 7ÛÏ 7ö 2Ëö ~º 1550 nm2Ë 'ö & º >êÚ ê2 ¢ B~º ~ ìº ;Þ .…”
unclassified
“…f PMT(photomultiplier tube)¢ ¦ÂV ÒÏ > ®º 633 nmöB 830 nm~ 2Ë 'ö &¦ª ÷7>î b, 7ÛÏ 7ö 2Ëö ~º 1550 nm2Ë 'ö & º >êÚ ê2 ¢ B~º ~ ìº ;Þ . [1][2][3][4] V¢B, öBº NSOMj Ï 7ÛÏ Ò ê2 ² ¶~ *2 ßWö &j <, ö ' NSOM G;Ë~¢ B·~&b, 2Ë 1550 nm 'öB Ò 7 ê2 ² ¶~ ö:JÎÞ 2 ª¢ G;~ 3D-FD BPM(3 Dimensional finite difference beam propagation method) Ö"f jv~ ~. º î'b ô ÒÏ> ®º 7 ÛÏ 7 ¶ ² ¶ö & ö £² wÏF > ®j ©b V&B.…”
unclassified
“…[11][12][13][14][15][16][17][18][19] Our first look into a cylindrical integrated optical microcavity by means of photon tunneling with a resolution of 50 nm revealed a variety of phenomena 19 such as polarization conversion, 20 copropagation, and even counterpropagation. WGM's at the surfaces of microspheres, the bulk-optics equivalent of our resonators, 19 have been measured by Knight et al, 21 and in a glass microring resonator by Vander Rhodes et al, 22 by means of photon tunneling.…”
Section: Introductionmentioning
confidence: 99%